KEPENARIAN ADI PUTRA CAHYA NUGRAHA DALAM TARI NGREMA BOLET JOMBANGAN - Utomo, Catur Prayogo; Soemaryatmi, Soemaryatmi (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
This research explores two main issues related to the form, technique, and performance quality of Adi Putra Cahya Nugraha in the Ngrema Bolet Jombangan dance: (1) the formal structure of the Ngrema Bolet Jombangan dance, and (2) the characteristics of Adi Putra Cahya Nugraha’s performance in terms of dance technique and expression. The study is grounded in the theoretical perspectives of Alma M. Hawkins on dance form, Sumandiyo Hadi’s theories of form and technique, and Tri Broto Wibisono’s concept of asisapapongolati. Using a qualitative research methodology with a choreographic approach, data were collected through field observation, interviews, and documentation. The findings reveal that the Ngrema Bolet Jombangan dance is a traditional folk dance with a warrior theme, performed in solo, duet, or group formations. Its structure consists of four main sections: (A) Ajon-ajon (opening), solah kanuragan, and isen; (B) Solah kridha and solah busana; (C) Solah budhalan; and (D) Pungkasan (closing). Adi Putra Cahya Nugraha, as the pengreman (lead dancer), demonstrates refined technical abilities and expressive qualities consistent with the principles of asisapapongolati. His dance practice incorporates both ritualistic and technical preparation, including nyebeng, nyajen, and gladen. Additionally, Adi showcases a personal stylistic identity through specific movement techniques such as adeg tanjak, saduk sampur, selentik sampur, and gantungan jaranan. This study contributes to the understanding of individual interpretation within traditional dance forms and highlights the role of personal style in sustaining and innovating cultural performance practices.